2021
DOI: 10.3390/ijms22147553
|View full text |Cite
|
Sign up to set email alerts
|

Maturity Onset Diabetes of the Young—New Approaches for Disease Modelling

Abstract: Maturity-onset diabetes of the young (MODY) is a genetically heterogeneous group of monogenic endocrine disorders that is characterised by autosomal dominant inheritance and pancreatic β-cell dysfunction. These patients are commonly misdiagnosed with type 1 or type 2 diabetes, as the clinical symptoms largely overlap. Even though several biomarkers have been tested none of which could be used as single clinical discriminator. The correct diagnosis for individuals with MODY is of utmost importance, as the appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 162 publications
2
6
0
Order By: Relevance
“…This result was accordant with a previous study on Chinese participants which concluded that individuals with KLF11-MODY7 and PAX4-MODY9 were found to have a higher BMI [39]. However, due to their rarity, the characteristics of these MODY subtypes have not been completely elucidated [25]. Regarding GCK-MODY2, these carriers typically exhibit mild hyperglycemia with an OGTT glucose increment of less than 60 mg/dl in European individuals.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This result was accordant with a previous study on Chinese participants which concluded that individuals with KLF11-MODY7 and PAX4-MODY9 were found to have a higher BMI [39]. However, due to their rarity, the characteristics of these MODY subtypes have not been completely elucidated [25]. Regarding GCK-MODY2, these carriers typically exhibit mild hyperglycemia with an OGTT glucose increment of less than 60 mg/dl in European individuals.…”
Section: Discussionsupporting
confidence: 88%
“…We estimated the prevalence of MODY at 1.77% of diabetes patients. Although in Europe the most prevalent subtypes are HNF1A-MODY3 and GCK-MODY2, in the MENA region, MODY prevalence is mainly unexplored [25,[38][39][40]. According to our ndings, INS-MODY10 was the most common type of MODY accounting for 46.6% of all mutations in Iranian participants.…”
Section: Discussionmentioning
confidence: 84%
“…MODY is not progressively mild, characterized by persistent fasting hyperglycemia, presence of residual pancreatic function, negative for diabetes-associated antibodies, non-insulin-dependent and involvement across multiple generations within a family. 1 , 2 …”
Section: Discussionmentioning
confidence: 99%
“…An estimated 1-5% of cases of diabetes are caused by conditions other than those mentioned above, including those with a genetic background and those that are non-genetically related. Types of diabetes with a genetic background are neonatal diabetes [14] and maturity-onset diabetes in the young [15], Wolfram syndromerelated (type 1) diabetes [16], and cystic fibrosis-related (type 1) diabetes [17]. Types of diabetes with a non-genetic background are, among others, chronic pancreatitisassociated diabetes, which is usually caused by extensive damage to the exocrine tissue of the pancreas [18], brittle diabetes, which primarily affects patients with type 1 diabetes and manifests as frequent and severe fluctuations in blood glucose levels [19], and Cushing's syndrome-related diabetes [20].…”
Section: Diagnosis and Subtypesmentioning
confidence: 99%